Kossinna Meets the Nordic Archaeologists - Evert Baudou (Current Swedish Archaeology, 2005)
The author discusses Montelius's, Aspelin's and Kossinna's ethnohistoric research and the development up to 1951.The starting point is a letter written by Kossinna in 1896 to Montelius in Stockholm. Kossinna's Siedlungsgeschichte and his tribal principle that cultural areas or cultural groups embodied a "Valk", are based on Montelius's paper from 1884/88 on the immigration ofthe ancestors of the Scandinavian peoples. Stringent European critics pointed out that Kossinna's method lacks any viable basis in theory. In spite of this the Scandinavian archaeologists continued the ethnohistoric tradition. In Finland there was marked criticism during the 1930s